(untitled) (FAVE Sección Ciencias Veterinarias, 2016)
The aim of this study was to detect species of Rickettsia in Amblyomma tigrinum ticks collected from domestic carnivores and blood of domestic dogs of San Luis (Argentina). Between 2013 and 2015, 56 adults of A. tigrinum from dogs and cats and 65 blood from dogs were collected. Three ticks were positive by amplification of a 23S-5S rRNA fragment, and the sequence of one of the positive products was obtained. The positive sample sequenced was positive by PCRs of fragments of genes gltA and ompA. The sequences obtained were 100% identical with "Candidatus Rickettsia andeanae". All blood samples were negative. “Ca. R. andeanae” has not been associated with disease in humans or animals; however, further research is necessary to achieve greater awareness of the potential risk of transmission of rickettsial diseases in the region.